23rd Annual Meeting of the German Professional Association of Travel Medicine (DFR) Coburg, Germany, 18-19. September 2020 - Günter Schmolz (Health Promotion & Physical Activity, 2020)
The publication contains summaries of papers presented at the annual meeting of German Professional Association of Travel Medicine (DFR) • J. Hinkelbein: In-flight Medical Emergencies (IFME) • N. Kohls: Promoting health by traveling: Mindfulness and travel medicine • Th. Küpper: Pandemias – are we really prepared? • M. Posch, G. Ruedl: Fatalities during recreational alpine skiing: A 10-year analysis from the Austrian Alps • K. Rinnert: Diabetes and driving ability • R. Steffen: Travel medicine news